Central Administration of Hydrogen Sulfide Donor NaHS Reduces Iba1-Positive Cells in the PVN and Attenuates Rodent Angiotensin II Hypertension - Donertas Ayaz, Basak; Oliveira, Aline C.; Malphurs, Wendi L.; Redler, Ty; de Araujo, Alan Moreira; Sharma, Ravindra K.; Sirmagul, Basar; Zubcevic, Jasenka (Frontiers in Neuroscience, 2021)
Hydrogen sulfide (H2S) is a gaseous signaling molecule with neuromodulatory, anti-inflammatory and anti-hypertensive effects. Here, we investigate whether chronic intracerebroventricular (ICV) infusion of NaHS, an H2S donor, can alleviate angiotensin (Ang) II-induced hypertension (HTN), improve autonomic function, and impact microglia in the paraventricular nucleus (PVN) of the hypothalamus, a brain region associated with autonomic control of blood pressure (BP) and neuroinflammation in HTN. Chronic delivery of AngII (200ng/kg/min, subcutaneous) for four weeks produced a typical increase in BP and sympathetic drive and elevated the number of ionized calcium binding adaptor molecule 1 positive (Iba1+) cells in the PVN of male, Sprague-Dawley rats. ICV co-infusion of NaHS (at 30 and/or 60 nmol/h) significantly attenuated these effects of AngII. AngII also increased the abundance of cecal Deltaproteobacteria and Desulfovibrionales, among other, which was prevented by ICV NaHS co-infusion at 30 and 60 nmol/h. We observed no differences in circulating H2S between the groups. Our results suggest that central H2S may alleviate rodent HTN independently from circulating H2S via effects on autonomic nervous system and PVN microglia.